Upaya Mengurangi Prokrastinasi Akademik Melalui Layanan Bimbingan Kelompok Dengan Teknik Diskusi Kelompok Pada Peserta Didik Kelas X Di SMAN 1 Kediri - Salsabila Putri Lintang Pertiwi; Isfauzi Hadi Nugroho; Lely Yuanita Permata Sari (Jurnal Pendidikan Sosial Dan Konseling, 2025)
Academic procrastination refers to the tendency to delay the completion of academic tasks, such as school assignments and other academic activities. Based on direct observation and the analysis of an academic procrastination questionnaire, this study found that six students from class X-B demonstrated a high level of academic procrastination, with an average score of 81.5. The research employed a Guidance and Counseling Action Research (PTBK) approach, aiming to reduce students’ academic procrastination through group counseling services using group discussion techniques. Data were analyzed using a descriptive comparative method. The results showed a significant reduction in academic procrastination levels among the subjects after participating in the counseling sessions. Before the intervention, the average score of the students was 81.5, which falls into the high category. After the first cycle of counseling, the average score decreased to 63.2, indicating a moderate level. Following the second cycle, the average score further dropped to 53.3, placing it in the low category. These findings suggest that group counseling services implemented through group discussion techniques are effective in reducing academic procrastination.